2020
DOI: 10.1155/2020/4242789
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Overweight and Obesity among Long-Distance Truckers in Ethiopia

Abstract: Background. Abnormal body mass index (BMI ≥ 25 kg/m2) has become a major global public health problem which is rising at a faster rate in urban areas of low- and middle-income countries. In Ethiopia, the prevalence gradually increases. Long-distance truckers are at a high risk of developing overweight or obesity due to the sedentary nature of their job. Despite these populations at a high risk of developing overweight/obesity such as drivers elsewhere, pieces of data that showed the prevalence and contributing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“… 75 78–81 89 Looking at the distribution of overweight or obesity, the prevalence span from 9.7% from a nationwide study 82 to 56.5% in a study conducted in Addis Ababa. 87 The pooled prevalence of overweight/ obesity was estimated at 23.9% (95% CI 19.9% to 28.0%, certainty of evidence: low). The presence of substantial heterogeneity in the included studies (I 2 =98.8%; p < 0.001) decreased the certainty of the evidence ( figure 3 and online supplemental table 2 ).…”
Section: Resultsmentioning
confidence: 98%
“… 75 78–81 89 Looking at the distribution of overweight or obesity, the prevalence span from 9.7% from a nationwide study 82 to 56.5% in a study conducted in Addis Ababa. 87 The pooled prevalence of overweight/ obesity was estimated at 23.9% (95% CI 19.9% to 28.0%, certainty of evidence: low). The presence of substantial heterogeneity in the included studies (I 2 =98.8%; p < 0.001) decreased the certainty of the evidence ( figure 3 and online supplemental table 2 ).…”
Section: Resultsmentioning
confidence: 98%
“…The use of psychoactive substances such as alcohol and chat leaves has become one of the rising major public health and socioeconomic problems worldwide, which is a particularly growing concern in Ethiopia [ 25 ]. Psychoactive substances are associated with a multiplicity of noncommunicable diseases and their risks and musculoskeletal disorders [ 26 28 ]. Truck drivers are important contributors to the economy of every country, especially in those with limited rail [ 10 ], water, and other forms of transport of goods.…”
Section: Introductionmentioning
confidence: 99%
“…Of these high SES/income groups, 17.65% were either overweight/obese. Among 28 included articles in a meta-analysis, five studies [20,21,[32][33][34] did not show significant association while the rest 22 studies [12][13][14]16,17,19,[22][23][24][25][26][27]32,[35][36][37][38][39][40][41][42][43] showed a positive association between high SES/income and obesity/ overweight. The pooled effect size revealed that the likelihood of being overweight/obese is 2.35 times higher (AOR = 1.89, 95% CI: 1.75, 2.04) among high SES or high income groups compared to the low SES or income groups, heterogeneity test: Tau = 0.25, I 2 = 84%, df = 26, p ≤ 0.001.…”
Section: Association Of Socioeconomic Status With Overweight/obesitymentioning
confidence: 99%